Analisis Pembiayaan Konsumtif Riil Pada Bank Syariah Di Indonesia - Rizky Maulana Pribadi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The objective of this research study is to study there is positive influence of Gross Domestic Product/GDP Real and Consumer Price Index of Financing Real, investigate the determinants of real financing consumtive at Islamic Bank in Indonesia and how the determinants change the real financing consumtive at Islamic Bank in Indonesia in period 2011-2016. The result show that the respond of Consumer Price Index/CPI, GDP Real, and it could be seen from its size which are 3.118983, 1.601941, 0.397987. From the result, it can be concluded that Real Financing Consumtive is influenced by IHK, GDP Real, and Real Financing Consumtive.